Spontaneous colonic perforation- rare presentation. - Kumar A; Griwan MS; Pal N (Department of Surgery, UKM Medical Centre, 2013)
Spontaneous perforation of the sigmoid colon or rectum is defined as a sudden colonic perforation in the absence of any known diseases like tumors, diverticulosis or external injury. It is a very uncommon finding, and if neglected, results in severe peritonitis, sepsis and high mortality. Colonic perforation treatment is also under review due to morbidity of colostomy and its closure later on for the patient. Spontaneous colonic perforation is more common in extremes of ages but no age is exempted from it.